Effects of Roxadustat on the Anemia and Iron Metabolism of Patients Undergoing Peritoneal Dialysis - Hirai, Keiji; Nonaka, Hiroaki; Ueda, Moeka; Morino, Junki; Kaneko, Shohei; Minato, Saori; Mutsuyoshi, Yuko; Yanai, Katsunori; Ishii, Hiroki; Matsuyama, Momoko; Kitano, Taisuke; Aomatsu, Akinori; et al. (Frontiers in Medicine, 2021)
Background: We investigated the effects of roxadustat on the anemia, iron metabolism, peritoneal membrane function, and residual renal function; and determined the factors associated with the administration of roxadustat in patients who were undergoing peritoneal dialysis. Methods: We retrospectively analyzed the changes in hemoglobin, serum ferritin, transferrin saturation (TSAT), 4-h dialysate/plasma creatinine, and renal weekly urea clearance over the 24 weeks following the change from an erythropoiesis-stimulating agent (ESA) to roxadustat in 16 patients who were undergoing peritoneal dialysis and had anemia (Roxadustat group). Twenty-three peritoneal dialysis patients who had anemia and continued ESA served as a control group (ESA group). Results: There were no significant differences in hemoglobin, serum ferritin, TSAT, 4-h dialysate/plasma creatinine, or renal weekly urea clearance between the two groups at baseline. The hemoglobin concentration was significantly higher in the Roxadustat group than in the ESA group after 24 weeks (11.6 ± 1.0 g/dL vs. 10.3 ± 1.1 g/dL, p < 0.05), whereas the ferritin concentration and TSAT were significantly lower (139.5 ± 102.0 ng/mL vs. 209.2 ± 113.1 ng/mL, p < 0.05; and 28.1 ± 11.5% vs. 44.8 ± 10.4%, p < 0.05, respectively). The changes in 4-h dialysate/plasma creatinine and renal weekly urea clearance did not differ between the two groups. Linear regression analysis revealed that the serum potassium concentration correlated with the dose of roxadustat at 24 weeks (standard coefficient = 0.580, p = 0.019). Conclusion: Roxadustat may improve the anemia and reduce the serum ferritin and TSAT of the peritoneal dialysis patients after they were switched from an ESA, without association with peritoneal membrane function or residual renal function.